Changes in the legal conditions of transport biofuels in Poland on the background of the European Union - Borowski, Piotr F.; Golisz, Ewa; Waldemar, Izdebski (Technology audit and production reserves, 2014)
The legal environment and development conditions of transport biofuels were analyzed in this paper. Law conditions can be stimulating or inhibiting tool to develop new technologies, demand and supply. Authors also conducted the study about biofuels of 1st and 2nd generation. Great hopes are connected with the 2nd generation transport biofuels, which are produced from plants: non-energy or waste (e.g. FT-diesel, bio-DME spirit lignocellulosic bio-SNG). The 2 generation has better features for the reduction of greenhouse gas emissions than biofuels of the 1st generation (i.e.: bioethanol formed by alcohol fermentation of esterification and biodiesel from rapeseed oil). Furthermore, National Indicative Target (NIT) linked with the reduction of CO2 were mentioned at this work. Only certified biofuels will be able to be taken into account for the calculation of national biofuel consumption NIT in transport in particular Union countries.